“THERE ARE NO INNOCENTS HERE”. MICROCOLONIZATION OF DONBASS IN YEVHEN POLOZHIY’S NOVEL ‘ILOVAYS’K’ (2015) - Chertenko, Alexander (Porównania, 2019)
Alexander Chertenko, “THERE ARE NO INNOCENTS HERE”. MICROCOLONIZATION OF DONBASS IN YEVHEN POLOZHIY’S NOVEL ‘ILOVAYS’K’ (2015). “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 69-84. ISSN 1733-165X. Basing on Yevhen Polozhiy’s “Ilovays’k”, the article examines the discourse of microcolonization of Donbass which is central to Ukrainian literature dealing with Russian-Ukrainian war. Referring to compensatory quasi-imperial practices employed by former colonies, the microcolonization dispositive is interpreted here as a basic tool for cultural and political (re)appropriation of Donbass as a kind of “internal alien”. The results of its use are the dehumanization of the Donbass population and its exclusion from the commemoration of the “own” victims of war, the delegitimation of any regional identity deviating from Ukrainian national narrative and, therefore, the performative integration of Donbass into the project of “integral” Ukraine.